A greener approach to assess bioactive compounds in tropical pumpkin (Cucurbita moschata) using colorimetry - Kinsman, Megan E.; Serviss, Mary T.; Meru, Geoffrey; Chase, Carlene A.; Sargent, Steven A.; Simonne, Amarat; MacIntosh, Andrew J. (Frontiers in Sustainable Food Systems, 2024)
Bioactive compounds have been shown to promote healthy human development and protect against certain diseases including some cancers. Tropical pumpkins bred for consumption, such as calabaza (Cucurbita moschata), possess these compounds, though concentrations vary considerably between varieties. Bioactive compound quantification methods can be expensive, complex, and generate considerable hazardous waste. A predictive tool utilizing the relationship between extrinsic properties and tristimulus colorimetry values of calabaza would allow for significantly higher throughput with lower requirements for equipment, training, and laboratory consumables. Therefore, this study examined correlations between flesh color and bioactive compound quantities of several calabaza germplasm lines to assess the utility of a sustainable and portable predictive tool. Redness was found to correlate with increased ascorbic acid and total soluble solids content. Yellowness correlated with β-carotene equivalent carotenoids and ascorbic acid content. These results suggest that colorimetry may be a viable pre-screening technique for quantifying bioactive compounds in C. moschata.